Anonymous whistleblowers reply scheme based on secret sharing - HE Kun; HUANG Yajing; DU Ruiying; SHI Min; LI Siqin; CHEN Jing (Tongxin xuebao)
Existing anonymous communication systems that resisted traffic analysis could hide the identities of the communicating parties from the attacker. However, the identities of the communicating parties couldn’t be hidden from each other, and thus these systems did not apply to the scenario of anonymous whistleblowing and replying, where it was necessary to protect the identity of the whistleblower. To address this issue, an efficient anonymous whistleblower response scheme was proposed. With the technology of distributed point functions and secret sharing, the message was stored in two separate mailbox databases of non-colluding servers, so that the identity of the data receiver was hidden from the attacker. With the technology of secret sharing and encryption, the email address of the whistleblower was hidden, so that the receiving organization could reply without learning the whistleblower’s identity. The security analysis showed that the proposed scheme enabled the anonymity of both data receivers and whistleblowers at the same time. The experimental results show that compared to the Express scheme, the proposed scheme reduces the computational complexity during a reply to O(1) from O(logN), resulting in a 60% reduction in computational overhead for the receiving organization and a 50% reduction for the server.